Analisis Faktor-Faktor yang Mempengaruhi Kekambuhan Pasien Skizofrenia - Hendro Prima Mukti; Sukendro Sukendro; Dwi Noerjoedianto; Asparian Asparian; Willia Novita Eka Rini; Muldiasman Muldiasman (Poltekkes Kemenkes Palembang, 2026)
Background: Schizophrenia is a serious mental disorder that can affect an individual's thoughts, feelings, and behavior. Schizophrenia carries a high risk of relapse, requiring special attention to minimize relapse. Factors contributing to relapse include medication adherence, family support, healthcare provider support, and genetic history. Methods: This type of research is a quantitative correlation research with a cross-sectional design approach. The research sample consisted of 106 people using purposive sampling technique. The research instrument used was a questionnaire. Data analysis was conducted univariately, bivariately with chi-square test and multivariately with multiple regression test.Written 3-5 sentences , conclusion Results: This type of research is a quantitative correlation research with a cross-sectional design approach. The research sample consisted of 106 people using purposive sampling technique. The research instrument used was a questionnaire. Data analysis was conducted univariately, bivariately with chi-square test and multivariately with multiple regression test. Conclusion: The most influential factor in the relapse of schizophrenia patients is genetic factors. It is hoped that families and hospitals will pay attention to factors that can cause relapse in schizophrenia patients.